TGF-β inhibits IL-7-induced proliferation in memory but not naive human CD4+ T cells. Issue 2 (6th June 2017) - Nguyen, Thao P; Sieg, Scott F
Abstract : TGF- β differentially impairs IL-7-induced proliferation in memory and naiüve CD4+ T cells. Abstract: TGF-β is a potent suppressor of T cell activation and expansion. Although the antiproliferative effects of TGF-β are well characterized in TCR-activated cells, the effects of TGF-β on T cell proliferation driven by homeostatic cytokines, such as IL-7, are poorly defined. In the current study, we found that TGF-β inhibits IL-7-induced proliferation in memory, but not in naive human CD4 + T cells. TGF-β impaired c-myc induction in all CD4 + T cell maturation subsets, although the impairment was less sustained in naive CD4 + T cells. TGF-β had no discernible effect on IL-7R signaling (p-STAT-5, p-Akt, or p-S6) in memory T cells but selectively enhanced p-S6 signaling in naive T cells. The inhibitory effects of TGF-β on memory T cell proliferation were partially overcome by chemical inhibition of GSK-3, which also led to enhanced c-myc expression. These data suggest that TGF-β could play an important role in limiting homeostatic proliferation of memory T cells. Our observations also point toward a novel strategy to subvert TGF-β-mediated inhibition of memory T cells by targeting GSK-3 for inhibition.